2018
DOI: 10.5194/tc-12-1595-2018
|View full text |Cite
|
Sign up to set email alerts
|

Observations and simulations of the seasonal evolution of snowpack cold content and its relation to snowmelt and the snowpack energy budget

Abstract: Abstract. Cold content is a measure of a snowpack's energy deficit and is a linear function of snowpack mass and temperature. Positive energy fluxes into a snowpack must first satisfy the remaining energy deficit before snowmelt runoff begins, making cold content a key component of the snowpack energy budget. Nevertheless, uncertainty surrounds cold content development and its relationship to snowmelt, likely because of a lack of direct observations. This work clarifies the controls exerted by air temperature,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
91
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 45 publications
(91 citation statements)
references
References 93 publications
0
91
0
Order By: Relevance
“…For this study, the combination of snow, soil, and meteorological variables resulted in the largest effective intra‐snowpack contributing area of meltwater to snow LWC at the highest elevation site, AT (Figure ). Higher elevation snowpacks will generally have higher cold content magnitudes (Jennings, Kittel, et al ()), which can refreeze surface melt produced prior to the snowpack reaching isothermal conditions. Refrozen meltwater often takes the form of ice lenses that act as permeability barriers (Webb, Fassnacht, Gooseff, et al, ) for later formation of meltwater intra‐snowpack flow paths as observed in this study (Table and Figure ).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…For this study, the combination of snow, soil, and meteorological variables resulted in the largest effective intra‐snowpack contributing area of meltwater to snow LWC at the highest elevation site, AT (Figure ). Higher elevation snowpacks will generally have higher cold content magnitudes (Jennings, Kittel, et al ()), which can refreeze surface melt produced prior to the snowpack reaching isothermal conditions. Refrozen meltwater often takes the form of ice lenses that act as permeability barriers (Webb, Fassnacht, Gooseff, et al, ) for later formation of meltwater intra‐snowpack flow paths as observed in this study (Table and Figure ).…”
Section: Discussionmentioning
confidence: 99%
“…We used the physics‐based SNOWPACK model (Bartelt & Lehning, ; Lehning, Bartelt, Brown, & Fierz, ; Lehning, Bartelt, Brown, Fierz, & Satyawali, ) to simulate snowmelt rates at the study sites. Model set‐up was the same as described in Webb, Jennings, Fend, and Molotch () and Jennings, Kittel, & Molotch () with the addition of the BTN site. We ran the model at an hourly time step using quality controlled air temperature, relative humidity, wind speed, incoming shortwave radiation, incoming longwave radiation, and snow depth data (Table ).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations